Room‐Temperature Direct Synthesis of Tetragonal β‐CsPbI3 Nanocrystals. Issue 2 (10th November 2021) - Chen, Dejian; Huang, Decai; Yang, Mingwei; Xu, Kunyuan; Hu, Jie; Xu, Feixiang; Liang, Sisi; Zhu, Haomiao
Abstract: Phase engineering of CsPbI3 nanocrystals (NCs) is a priority for their optoelectronic applications. So far, the scalable and room‐temperature direct synthesis of black phase CsPbI3 NCs remains an enormous challenge because of the thermal unequilibrium‐induced phase transition. Herein the direct synthesis is reported of metastable β‐CsPbI3 NCs in gram‐scale at room‐temperature in seconds via spontaneous crystallization. The obtained β‐CsPbI3 NCs exhibit good monodispersity, narrow‐band far‐red emission (716 nm, FWHM = 38 nm) as well as a high photoluminescence quantum yield of 62%. The crystallization dynamics of β‐CsPbI3 NCs are revealed through in situ UV–vis absorption and photoluminescence spectra analysis. Finally, a photon‐to‐photon conversion indirect X‐ray detector based on the phase‐stable NCs/polystyrene film is preliminarily demonstrated. This scalable and low‐cost preparation of high‐quality metastable β‐CsPbI3 NCs will pave the way for their future commercial applications in novel optoelectronic devices. Abstract : Phase stable β‐CsPbI3 nanocrystals with high photoluminescence quantum yield (62%) are first synthesized at room temperature through a spontaneous crystallization method, which is convenient for large‐scale production in an environmentally friendly way.